Public procurement and access to justice: a legal and empirical study of the UK system - Arrowsmith, Sue; Craven, Richard (Sweet and Maxwell, 2016)
This article presents the findings of an empirical study into suppliers’ behaviour in enforcing EU public procurement law in the UK - where there is a low level of procurement litigation – and the factors influencing this. The study indicates that most suppliers have not perceived any breaches of EU procurement law. It also indicates that, for cases where problems are perceived, recent reforms required by EU law have led to more complaints and legal actions, and enhanced the practical effectiveness of remedies. However, the study also reveals important remaining obstacles to litigation, in particular the high cost of High Court proceedings, fear of reprisals and (although to a lesser extent) the courts’ approach to interim relief. In the light of recent case law, these findings have interesting implications for the UK’s compliance with its EU obligations to provide effective supplier remedies, and suggest a need to consider a different approach.